PRDM9 interactions with other proteins provide a link between recombination hotspots and the chromosomal axis in meiosis - Parvanov, Emil D; Tian, Hui; Billings, Timothy; Saxl, Ruth L; Spruce, Catrina; Aithal, Rakesh; Krejci, Lumir; Paigen, Kenneth; Petkov, Petko M (Molecular biology of the cell, 2017)
In mammals, meiotic recombination occurs at 1- to 2-kb genomic regions termed hotspots, whose positions and activities are determined by PRDM9, a DNA-binding histone methyltransferase. We show that the KRAB domain of PRDM9 forms complexes with additional proteins to allow hotspots to proceed into the next phase of recombination. By a combination of yeast-two hybrid assay, in vitro binding, and coimmunoprecipitation from mouse spermatocytes, we identified four proteins that directly interact with PRDM9's KRAB domain, namely CXXC1, EWSR1, EHMT2, and CDYL. These proteins are coexpressed in spermatocytes at the early stages of meiotic prophase I, the limited period when PRDM9 is expressed. We also detected association of PRDM9-bound complexes with the meiotic cohesin REC8 and the synaptonemal complex proteins SYCP3 and SYCP1. Our results suggest a model in which PRDM9-bound hotspot DNA is brought to the chromosomal axis by the action of these proteins, ensuring the proper chromatin and spatial environment for subsequent recombination events.
Keywords: chromatin; Chromatin; dvouřetězcové zlomy DNA; zvířata; Male; rekombinace genetická; meióza; genom; proteinové domény; Homologous Recombination; Mice; Genome; Animals; Protein Domains; mužské pohlaví; chromozomy; DNA Breaks, Double-Stranded; DNA; Spermatocytes; Histone-Lysine N-Methyltransferase; spermatocyty; histonlysin-N-methyltransferasa; Chromosomes; Recombination, Genetic; Meiosis; homologní rekombinace; myši